Penerapan Literasi Digital dalam Aktivitas Pembelajaran Daring Mahasiswa - Yuni Fitriani; Roida Pakpahan; Bambang Junadi; Handini Widyastuti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Abstract: In following the development of information technology, each individual is also required to be able to understand the concept of digital literacy, because with the understanding and application of digital literacy, each individual can participate and adapt in today's digital era. Digital literacy is also a literacy that is in line with the demands of learning transformation in the world of education during the Covid-19 pandemic. The application of digital literacy in students' online learning activities in this study is seen from the characteristics of student activities in online learning which include learning spirit, literacy in technology, ability to communicate interpersonally, collaborate and self-study skills. This study uses qualitative descriptive methods. Based on the results of research that the application of digital literacy in student online learning activities is quite good. Where with the application of digital literacy, students are still passionate about learning even though learning is carried out online with various technological media and digital devices. Students also have the ability to digital literacy in terms of mastery of technological media that supports online learning, able to collaborate with other students and lecturers by using online communication media in the digital space and have self-study skills.